Establishing the effect of a simultaneous reduction in the filling load inside a chamber and in the content of the crushed material on the energy intensity of self-oscillatory grinding in a tumbling mill - Deineka, Kateryna; Naumenko, Yuriy (Eastern-European Journal of Enterprise Technologies, 2021)
The effect of a simultaneous change in the degree of filling a chamber with load κbr and in the content of the crushed material κmbgr on the efficiency of the self-oscillatory grinding process has been estimated. Using a method of numerical modeling based on the results of experimental visualization of the flow has helped establish an emergent dynamic effect of the sharp increase in the self-oscillatory action of two-faction loading at a joint reduction in κbr and κmbgr. A significant decrease in the passive quasi-solid loading motion zone has been detected, as well as an increase in the active pulsation zone and a growth of dilatancy. The manifestation of the effect is enhanced by the simultaneous interaction of increasing the scope of self-oscillations and weakening the coherent properties of particles in a loose large fraction under the influence of the particles of fine fraction. A significant decrease in the values of the inertial loading parameters has been established: maximum dilatancy υmax, the relative scale of self-oscillations ψRυ, the maximum share of the active part of κfammax, and the generalized complex degree of dynamic activation Ka. A 2.65-time growth of υmax was detected, ψRυ increased by 5 times, κfammax ‒ by 4.36 times, Ka ‒ by 18.4 times, at a joint decrease in κbr from 0.45 to 0.25, in κmbgr ‒ from 1 to 0. The synergistic technological effect of a sharp decrease in the specific energy intensity Еo/Еs has been established, as well as an increase in the relative performance Co/Cs in the self-oscillatory grinding, due to a significant increase in the dynamic action of loading, which is exacerbated by the joint interaction of reduced κbr and κmbgr. The process of the self-oscillatory grinding of cement clinker has been investigated. A 62 % reduction in Еo/Еs and a 125 % increase in Co/Cs were detected at a joint decrease in κbr from 0.45 to 0.25, in κmbgr ‒ from 1 to 0.125. The established effects make it possible to substantiate the parameters for the energy-efficient self-oscillatory process of grinding in tumbling mills with a conventional structure